Edukasi Santri Dalam Upaya Pencegahan Wabah Virus Covid – 19 Di Pondok Pesantren Sumbersari Kencong Kepung Kediri - M. Nur Kholiq (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
Educating students in an effort to prevent the Covid-19 virus outbreak is a learning process from not knowing to know. Student-centred to conduct an in-depth investigation of a topic. This study aims to find out how to prevent the spread of the Covid-19 virus outbreak in the pesantren environment. The research method used is the PAR method or Participatory Action Research. The subjects of this study were the students of the Sumbersari Kencong Islamic boarding school, Kepung, Kediri, East Java. The results showed that students were able to try to prevent the Covid-19 virus outbreak with 5M education as a new covid prevention step required to break the spread of covid-19 that had not been conveyed widely in Islamic boarding schools.